Zawód mediator. Kilka uwag w kontekście refleksji nad wyzwaniami wobec kariery zawodowej współczesnej młodzieży = Occupation - mediator. Some remarks in the context of reflection over the challenges of professional career of contemporary youth - Urbaniak, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Contemporary expectations towards employees or job applicants often refer not so much to the demand for specifically defined skills, which may be acquired within the frames of clearly outlined educational paths, but to the flexibility, openness to change, initiative, entrepreneurship, willingness to continuous learning and multidirectional professional development at every stage of an employee`s career.
Keywords: mediation; youth; profession; professional flexibility; mediacja; młodzież; zawód; elastyczność zawodowa